(untitled) (American Journal of Public Diplomacy and International Studies (2993-2157), 2025)
This article analyzes the issue of combating corruption, which is one of the important conditions for building a just society in the Republic of Uzbekistan today, the formation of an anti-corruption culture, and its local characteristics